21st century guidebook to fungi - Moore, David; Robson, G. D. (Geoffrey D.); Trinci, Anthony P. J. (Cambridge : Cambridge University Press, 2020)
The mysterious world of fungi is once again unearthed in this expansive second edition. This textbook provides readers with an all-embracing view of the kingdom fungi, ranging in scope from ecology and evolution, diversity and taxonomy, cell biology and biochemistry, to genetics and genomics, biotechnology and bioinformatics. Adopting a unique systems biology approach - and using explanatory figures and colour illustrations - the authors emphasise the diverse interactions between fungi and other organisms. They outline how recent advances in molecular techniques and computational biology have fundamentally changed our understanding of fungal biology, and have updated chapters and references throughout the book in light of this. This is a fascinating and accessible guide, which will appeal to a broad readership - from aspiring mycologists at undergraduate and graduate level to those studying related disciplines. Online resources are hosted on a complementary website.
1: Twenty-first century fungal communities -- 2: Evolutionary origins -- 3: Natural classification of fungi -- 4: Hyphal cell biology and growth on solid substrates -- 5: Fungal cell biology -- 6: Fungal genetics: from gene segregation to gene editing -- 7: Structure and synthesis of fungal cell walls -- 8: From the haploid to the fungal diploid: homokaryons, dikaryons and compatibility -- 9: Sexual reproduction: the basis of diversity and taxonomy -- 10: Continuing the diversity theme: cell and tissue differentiation -- 11: Fungi in ecosystems -- 12: Exploiting fungi for food -- 13: Development and morphogenesis -- 14: Ecosystem mycology: saprotrophs and mutualisms between plants and fungi -- 15: Fungi as symbionts and predators of animals -- 16: Fungi as pathogens of plants -- 17: Fungi as pathogens of animals, including humans -- 18: Killing fungi: antifungals and fungicides -- 19: Whole organism biotechnology.
Title from publisher's bibliographic system (viewed on 02 Dec 2021).
Keywords: elektronické knihy; electronic books; Fungi; Fungal molecular biology